DBP alteration from NOM and model compounds after UV/persulfate treatment with post chlorination. (1st July 2019) - Hua, Zhechao; Kong, Xiujuan; Hou, Shaodong; Zou, Shiqian; Xu, Xibing; Huang, Huang; Fang, Jingyun
Abstract: The UV/persulfate process is an effective advanced oxidation process (AOP) for the abatement of a variety of micropollutants via producing sulfate radicals (SO4 - ). However, when this technology is used to reduce target pollutants, the precursors of disinfection byproducts (DBPs), such as natural organic matter (NOM) and organic nitrogen compounds, can be altered. This study systematically investigated the DBP formation from NOM and five model compounds after UV/H2 O2 and UV/persulfate treatments followed with 24 h chlorination. Compared to chlorination alone, the yields of trichloromethane (TCM) and dichloroacetonitrile (DCAN) from NOM decreased by 50% and 54%, respectively, after UV/persulfate treatment followed with chlorination, whereas those of chloral hydrate (CH), 1, 1, 1-trichloropropanone (1, 1, 1-TCP) and trichloronitromethane (TCNM) increased by 217%, 136%, and 153%, respectively. The effect of UV/H2 O2 treatment on DBP formation shared a similar trend to that of UV/persulfate treatment, but the DBP formation was higher from the former. As the UV/persulfate treatment time prolonged or the persulfate dosage increased, the formation of TCM and DCAN continuously decreased, while that of CH, 1, 1, 1-TCP and TCNM presented an increasing and then decreasing pattern. SO4 - activated benzoic acid (BA) to form phenolic compounds that enhanced the formation of TCM and CH, while it deactivated resorcinol to decrease the formation of TCM. SO4 - reacted with aliphatic amines such as methylamine (MA) and dimethylamine (DMA) to form nitro groups, which significantly increased the formation of TCNM in post chlorination, and the rate was determined to be higher than that of HO . This study illuminated the diverse impacts of the structures of the precursors on DBP formation after UV/persulfate treatment, and DBP alteration depended on the reactivity between SO4 - and specific precursor. Graphical abstract: Image 1 Highlights: SO4 - oxidation decreased the TCM and DCAN formation but increased the TCNM and CH formation from NOM chlorination. SO4 - oxidation dramatically increased the TCNM formation from aliphatic amines. SO4 - activated benzoate but deactivated resorcinol to form TCM and CH. SO4 - oxidation showed differences from HO in DBP alteration from NOM and model compounds. DBP alteration by UV/persulfate treatment depended on the precursor structures and water matrices.